Performance Of Zwitterionic Adsorbent Coating For Real Industrial Effluents - Yoganathan, Kartiyani (Universiti Sains Malaysia, 2021)
In this report zwitterionic adsorbent coatings are used to reduce color intensity, chemical oxygen demand (COD) and zinc metal. Industrial waste is collected from Jabi Landfill, Kedah and Muda Paper Mills SDN. BHD, Penang. Adsorption performance was evaluated in terms of color, COD, zinc removal and pH. The ‘one -factor-at-a-time’ (OFAT) approach was used to study the effects of each factor. The number of adsorbent bands, temperature and pH were among the adjusted variables in this experiment. Comparatively the samples from the landfill showed a significant decrease in wastewater parameters with the help of zwitterionic adsorbent strips. Optimal conditions for adsorption are through the use of 2 adsorbent strips (color: 76.01%, COD: 74.73%and Zn (II): 63.16%), at a temperature of 80 ℃ (color: 41.61%, COD: 73.91%and Zn (II): 47.37%) and pH 7 (color: 57.55%, COD: 74.46%and Zn(II): 57.89%). The morphology and functional groups of the adsorbent before and after the process were characterized using SEM-EDX analysis. Based on the images obtained, the molecules attached to the cotton fiber network can be observed. Meanwhile, elements such as Vanadium (V), Cobalt (Co), Nickel (Ni), Chromium (Cr), Lead (Pb), Calcium (Ca), etc. can be derived from industry waste can be seen from the top of the EDXgraph.